Multidetector Computed Tomography Angiography Findings of Chronic-Contained Thoracoabdominal Aortic Aneurysm Rupture with Severe Thoracal Vertebral Body Erosion - Ruken Yuksekkaya; Ali Ekrem Koner; Fatih Celikyay; Murat Beyhan; Ferdag Almus; Berat Acu (Case Reports in Radiology)
Chronic-contained aortic aneurysm rupture with vertebral erosion is a rare entity with fatal complications. Multidetector computed tomography (CT) angiography is an important diagnostic method for the evaluation of the aortic aneurysms, their complications, and also the relationship between aneurysm and branching vessels and adjacent structures. We present the multidetector CT angiography findings of a 62-year-old patient with chronic-contained thoracoabdominal aortic aneurysm rupture causing severe vertebral body erosion.